PENGARUH VARIASI OKSIGEN TERHADAP LAJU KEMATANGAN KOMPOS - IDAA Warmadewanthi (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2003)
Rotatable reactors were used in this experiment. Oxygen was continously supplied into the reactors until the compost was mature. Using a motor, the rectors were rotated daily at a speed of 1.5 rpm for 5 revolutions. Domestic waste sludge was added to the reactor to have an initial C/N ratio of 30. The sludge was mixed with the compost before being inserted to the reactors. The results showed that oxygen of 9.07-114.4 l/kg.day was required in order a mature compost within 7 days. This was proved by having a C/N ratio of < 20 and stable temperature. The compost quality was adequate as shown by the pH of 6-8.5 with N concentration of 2.2-2.5%, P of 0.21% and K of 0.34%.